Omentopexy for patch repair of diaphragmatic defect - Mehrdad Hosseinpour; Mohadese Hamsaie; Abasat Mirzaei (Wolters Kluwer Medknow Publications, 2013)
Background: There are many techniques in the reconstructive of congenital diaphragmatic hernia defect. In this study, we present our results from a prospective, randomised trial of using the omentum (omentopexy) for repair of large diaphragmatic defects. Materials and Methods: Twenty white, male, New Zealand rabbits were used to compare incidence and severity of adhesion bands formation in abdominal cavity with/without of omentopexy after repair of diaphragm defect with the non-absorbable patch (Dacron). They were divided in to two groups, GI (10 animals with omentopexy and repair) and GII (10 animals with repair, without omentopexy). On the 60 th day, animals were re-operated. In each case, adhesion band formation and its severity were recorded. Results: The difference between the incidence of adhesion band formation among the two group was statistically significant (P = 0.019).The majority of rabbits in GII (60%) had substantial adhesion bands (Grade >2 or severe score), whereas, in GI, none of rabbits had substantial adhesion bands (P = 0.019). Conclusion: Our study showed that the use of omentopexy as a cover in repair of diaphragmatic defect is versatile technique with a good success for decreasing of adhesion band formations at short-term follow-up.